2015
DOI: 10.1016/j.ijrobp.2015.07.228
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Clinical Trial Combining Radiation Therapy With Systemic Immunotherapy in Metastatic Melanoma

Abstract: Purpose/Objective(s): Multiple preclinical studies and case reports have described synergistic interactions between radiation (RT) and checkpoint blockade immunotherapy (CBI), and the combination has the potential to enhance locoregional as well as systemic control. We previously described a role for RT in enhancing T cell activation and proliferation via antigen cross-presentation in the draining lymph node when combined with anti-PD-1 CBI. Here, we further define this role and specifically analyze the clonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 0 publications
1
25
0
3
Order By: Relevance
“…10 Furthermore, the rate of CR for the Ipi-RT group in our study was 25.7%, which closely matches the rate of CR in the prospective clinical trial (27.3%). 27 The rate of CR in the ipilimumab alone group (6.5%) was also close to the rate of CR reported in a previous phase III trial (1.5-11%). 6 This finding suggests that patients in this study who were treated with ipilimumab alone had a similar outcome to patients treated with ipilimumab in previous trials.…”
Section: Discussionsupporting
confidence: 86%
“…10 Furthermore, the rate of CR for the Ipi-RT group in our study was 25.7%, which closely matches the rate of CR in the prospective clinical trial (27.3%). 27 The rate of CR in the ipilimumab alone group (6.5%) was also close to the rate of CR reported in a previous phase III trial (1.5-11%). 6 This finding suggests that patients in this study who were treated with ipilimumab alone had a similar outcome to patients treated with ipilimumab in previous trials.…”
Section: Discussionsupporting
confidence: 86%
“…3 Preclinical models showed that this effect is largely immune mediated, 3,4 a finding further supported by associations in early clinical studies. [5][6][7][8] Importantly, these abscopal effects seldom occur after RT alone, suggesting that RT as a single agent is not sufficient to trigger an effective antitumor immune response in cancer patients. Abscopal effects more frequently emerge in patients treated with combined RT and immunotherapy (IT).…”
Section: Introductionmentioning
confidence: 99%
“…In the second, radiation therapy (determined by the treating radiation oncologist, ranged between 18 and 50 Gy in 1 to 15 fractions) was performed concomitantly with ipilimumab. Fifteen percent of patients achieved complete response with a median follow-up of 55 weeks and 15% achieved a partial response [ 43 ].…”
Section: Rt and Ici Synergism: Emerging Clinical Evidence Related mentioning
confidence: 99%